La dimension rituelle dans la videoperformance d’Orlan - Queiroz, Sheyna Teixeira (Mimesis Journal, 2018)
This article aims to stress the ritual in the context of the primitive, and the works of Orlan that have videoperformative properties. We aim to find the ritual elements in modern and contemporary videoperformance through these works. The methodology will follow research based on previous references of scientific and journalistic articles and by watching videos of selected works. The ritual dimension will be compared to everyday life to find out what social values are staged between the rite and the new technologies of the performative media.